THE PRINCIPAL'S SUPERVISION OBSERVATIONAL APPROACH TOWARDS TEACHERS’ PERFORMANCE AT SDN 12 BANTAN KABUPATEN BENGKALIS - Sumiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
School action research is a research that aims to improve learning methods and the results of the learning process in schools. This research was conducted at SDN 12 Bantan, Kecamatan Bantan, Kabupaten Bengkalis, with the teachers at SDN 12 Bantan as the subjects. The research method was descriptive, aiming to explain or describe the facts found in the field. The approach taken was observational supervision, which functioned to monitor and improve teachers’ ability in the learning process in order to achieve the objectives of learning. The results showed an increase in teachers’ activity during the learning process, starting in the first cycle of the first meeting with a percentage of 62% (fairly good category), followed by 64% in the second meeting (still fairly good). In the second cycle, during the third meeting, the percentage of teachers’ activity increased to 88% (very good category), and in the fourth meeting it reached 96% (very good category). Observations of teachers’ performance after the application of learning reflection in two cycles showed that teachers were able to master and understand teaching materials well, explain the material effectively, build a communicative classroom atmosphere, enjoy teaching, understand students’ experiences and abilities, use various teaching methods, eliminate less important materials, follow the latest developments in knowledge, and prepare learning processes that encouraged students to achieve better results. Overall, teachers were able to develop and apply their abilities effectively.